Rural radio programme evaluation workshop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
This workshop reviewed CTA's rural radio programme and put forward strategies for future activities in in many ACP countries. The proceedings contain the papers presented, working group reports and syntheses of surveys conducted prior the workshop.